Purification And Characterization Of Acrylamide-Degrading Enzyme From Burkholderia Sp. Dr.Y27 - Gusmanizar, Neni (2006)
Acrylamide is a toxic and carcinogenic compound. There are many sources of acrylamide pollution in soil. Three major documented sources are polyacrylamide used liberally as a flocculating agent in water treatment, acrylamide waste from acrylic industries, and the other is from the formulation in the herbicide glyphosate. It has been documented that approximately 0.1% of polyacrylamide is degraded yearly to the carcinogenic acrylamide in soil by soil bacteria. Some of the acrylamide is used as carbon and nitrogen sources by soil bacteria whilst it is suggested that the remaining becomes a source of contamination in vegetables and potatoes. Understanding acrylamide degradation in soil is vital not only to the microbiological point of view, but the prospect of lowering acrylamide concentrations via bioremediation would lower the potential of acrylamide as a pollutant and contaminant. Several local bacteria have been isolated from glyphosate-contaminated soils at various locations throughout Malaysia. Out of these isolates we have singled out a potent acrylamide-degrading bacterium, which could be potentially used in the bioremediation of acrylamide. Quantitative degradation of acrylamide was performed using High Performance Liquid Chromatography (HPLC), whilst bacterial growth was carried out by plate counting. Isolate 2.7 could degrade 99.84% of 100 mg/L acrylamide as the sole nitrogen source after 48 hours of incubation. Isolate 2.7 was identified as Burkholderia sp. Strain DR.Y27 using 16S rRNA and BiologTM microbial identification system. Burkholderia sp. Strain DR.Y27 showed an optimum temperature for growth at 30°C, and optimum initial pH medium for bacterial growth at pH 7.5. Burkholderia sp. strain DR.Y27 showed maximum growth in medium containing 1 % glucose and when 500 mg/L acrylamide was provided. The acrylamide-degrading enzyme, amidase, from this bacterium was stable at pH 8 when stored at 4 and -20 °C. Amidase activity was not affected by 1 mM of all metal ions tested, such as WO42-, L12+, Fe2+, As4+, Ni2+, Se2+, Zn2+, Cs2+, Cr2+, Al3+, Mn2+, Co2+, Mg2+, Cu2+, Pb2+, Cd2+, Ag2+, Hg2+, the enzyme activity also was not affected by EDTA, β-Merchaptoethanol and DTT. The maximum velocity in the order of decreasing rates using various substrates were 1.99 ± 0.11 Units/mg protein, 1.50 ± 0.09 Units/mg protein, 1.5 ± 0.02 Units/mg protein, 0.6 ± 0.04 Units/mg protein, 0.48± 0.01 Units/mg protein and 0.34 ± 0.02 Units/mg protein for propionamide, acrylamide, urea, acetamide and 2-cloroacetamide, respectively. The apparent Km for these substrates in the order of decreasing affinity are 0.27 ± 0.19 mM, 1.21 ± 0.13 mM, 1.88 ± 0.28 mM, 2.39 ± 1.84 mM and 4.29 ± 0.87 mM for acetamide, 2-cloroacetamide, urea, acrylamide and propionamide, respectively. The amidase from Burkholderia sp. strain DR.Y27 could not use metachrylamide and nicotinamide as substrate. The amidase exhibited maximal activity at 40°C and at pH 8.0 of phosphate buffer. The apparent Km and Vmax values for amidase were 2.39 ± 1.84 mM mM acrylamide and, 1.50 ± 0.09 μmol min-1 mg-1 protein, respectively using acrylamide as a substrate. The amidase was purified to homogeneity by a combination of anion exchange and gel filtration chromatography. The purification strategy achieved 11.15 of purification fold and a yield of 1.55%. Pure amidase showed a homogenous protein band with approximate MW of 186 kDa using gel filtration ZorbaxR GF-250 column chromatography. The purified enzyme migrated as a single band in SDS-PAGE in the presence of β-mercaptoethanol with a molecular mass of 47 kDa. It indicates that the native enzyme was a homotetramer.